AB0551 The use and effectiveness of rituximab in patients with rheumatoid arthritis observational study: Corrona registry. (23rd January 2014) - Harrold, L.; John, A.; Reed, G.; Reiss, W.; Magner, R.; Chung, C.Y.; Saunders, K.C.; Kremer, J.M.; Greenberg, J.D.
Abstract : Background: Little is known regarding the use and effectiveness of rituximab (RTX) in patients with rheumatoid arthritis (RA) in the United States. Using a cohort of 26, 877 patients with RA from 28-Feb-2006– 05-Dec-2011 from a multicenter observational registry within the U.S. (Consortium of Rheumatology Researchers of North America: CORRONA) we evaluated the use and effectiveness of RTX. Methods: Using data from CORRONA, we identified RA patients that initiated RTX with prior anti-TNF exposure (baseline visit) and were not in remission based on the Clinical Disease Activity Index (CDAI) at the time of initiation, with a follow-up visit at 1 year (±3 month) and at least 1 additional visit between baseline and 1 year visits. Outcomes assessed at 1 year included change in CDAI and the Disease Activity Score-28 joint (DAS-28), as well as achievement of remission (based on CDAI and DAS28). Rates of adverse events were identified. Results: We identified 265 patients that used RTX and met study inclusion criteria. Most patients were female (80%), rheumatoid factor seropositive (75%) with a median age of 57 (IQR 50-65), median disease duration of 13 years (IQR 7-22), and moderate to severe disease activity (median CDAI 22; IQR 13-33) at baseline. Most had prior exposure to nonbiologic disease modifying anti-rheumatic medications (DMARDs) (median 3; IQR 2-5) and biologics (median 2; IQR 1-3). RTX was commonly prescribed with a nonbiologic DMARD (77%) and prednisone (42%). Over the 1-year follow-up (outcomes in Table 1 ), 67% were retreated with RTX and 17% received a subsequent non-RTX biologic. Rates of cardiovascular events, serious infection, and malignancy were 1.9 (95% CI 0.6-4.0), 1.6 (95% CI 0.5-4.9), and 1.5 (95% CI 0.6-4.0) per 100 person-years, respectively. Conclusions: Patients initiating RTX had very active disease with prior exposure to several nonbiologic and biologic agents. Use of RTX was shown to be effective with a safety profile comparable to previous RTX clinical trials. Disclosure of Interest: L. Harrold Consultant for: CORRONA, A. John Employee of: Genentech, Inc, G. Reed Grant/Research support from: CORRONA, Consultant for: CORRONA, Employee of: University of Massachusetts Medical School, Paid Instructor for: Harvard Medical School, W. Reiss: None Declared, R. Magner: None Declared, C. Chung: None Declared, K. Saunders Employee of: CORRONA, J. Kremer Shareholder of: CORRONA, Grant/Research support from: Abbott, Amgen, AstraZeneca, BMS, Genentech, Lilly, Pfizer, Consultant for: Amgen, Genentech, Lilly, Pfizer, Employee of: CORRONA, Speakers Bureau: Abbott, Amgen, BMS, Pfizer, J. Greenberg Shareholder of: CORRONA, Consultant for: AstraZeneca, Novartis, Pfizer, CORRONA